A framework to guide developers in improving attractiveness and learnability of web applications - Ngadiman, Norzila (UNIVERSITI MALAYSIA PAHANG, 2016)
Attractiveness and learnability are the quality criteria that is strongly recommended during design and development of a software application mainly a Web application. They are sub-criteria under usability that are also known as operability under non-functional requirements in ISO/IEC 25020:2011. Besides functional requirements, an attractive Web application provides certain impact to users. However, attractiveness and learnability criteria have not been seriously applied in the Web application development, especially in Web design. Thus, a framework as a guideline to Web developers is vital to promote consideration of attractiveness and learnability when designing Web applications. A case study investigates the attractiveness and learnability sub-criteria in a Web application that provides an insight on how to improve this aspect by adopting the proposed framework.